The Role of Vitamin A, Vitamin C and Vitamin E for Chemoprevention of Oral Leukoplakia - Islam, Mohidul; Ali, Mir Nowazesh; Anwar, Rezwana Binte; Asaduzzaman , Md; Islam , A S M Ariful; Hussain, Mahbub; Rahman, Quazi Billur (Update Dental College Journal, 2023)
Introduction: Oral leukoplakia is a prevalent oral mucosal lesion known to undergo malignant transformation, posing a significant public health concern worldwide, primarily attributable to tobacco use. This study aims to investigate the potential preventive effects of vitamins A, C, and E on oral leukoplakia. We conducted a cross-sectional study at the Department of Oral & Maxillofacial Surgery, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, over a one-year period from March 2017 to March 2018. Methods: Study Population: We enrolled a total of 43 patients diagnosed with oral leukoplakia attending the Outpatient Department (OPD) of the Oral & Maxillofacial Surgery Department. Data Collection: Patients were assessed at 6, 12, and 24-week intervals, during which data were collected using standardized data sheets. Lesion size was measured in square centimeters, and lesion color was recorded through photography. Adverse drug reactions were monitored based on patient complaints during follow-up. Histopathological Evaluation: Histopathological evaluations were performed both before the study and at the conclusion of the study to assess any changes in tissue characteristics. Outcome Variables: The primary outcome variables of interest were clinical response, histopathological findings, and complications associated with the treatment. Results: The study population had a mean age of 44.95±10.42 years, with an age range from 22 to 60 years. The male-to-female ratio was 1.3:1. The average duration of the lesions was 14.81±4.82 months, with a range of 6 to 24 months. Lesions were most commonly located in the right buccal mucosa (41.9%), followed by the left buccal mucosa (27.4%). The mean initial lesion size was 4.08±1.95 cm², ranging from 1 to 8 cm². After 24 weeks, 11.63% of patients showed complete improvement. All patients initially presented with white lesions, with a reduction to 97.7% after 6 weeks, 88.4% after 12 weeks, and 69.8% after 24 weeks. Mild adverse drug reactions were reported in 11.7% of patients after 6 weeks and 2.3% after 12 and 24 weeks. Complete remission was observed in 11.6% of patients, and moderate improvement (41–90%) in 37.3%. Notably, one-third of patients experienced a significant color change in their lesions, and adverse drug reactions decreased during subsequent follow-up. Conclusion: This cross-sectional study indicates potential benefits of Vitamin A, Vitamin C, and Vitamin E in mitigating oral leukoplakia symptoms, such as reduced lesion size and color improvement, with fewer adverse reactions observed. However, larger, controlled trials are necessary to establish the definitive efficacy of this vitamin combination. Update Dent. Coll. j: 2023; 13(2): 23-29